Green recovery of pectic polysaccharides from citrus canning processing water. (15th February 2017) - Chen, Jianle; Cheng, Huan; Wu, Dan; Linhardt, Robert J.; Zhi, Zijian; Yan, Lufeng; Chen, Shiguo; Ye, Xingqian
Abstract: Canned citrus segments are popularly consumed worldwide with a large global market. However, the production needs chemical treatment to remove segments membranes, producing a large amount of acidic and basic effluents with very high chemical oxygen demand (COD), causing serious environmental problems. This research is focused on the plant scale recovery of pectic polysaccharides from the above acidic and basic processing water to decrease COD and develop a new product, through steps including water reuse (alternative), two-step filtration, concentration, ethanol precipitation and ethanol recovery. The yields of polysaccharides were 0.30% and 0.45% (w/v) from reused acidic and basic water, respectively, dramatically decreasing the COD by ∼75% from ∼10, 000 mg/L, and having a great estimated output value of ∼$1.8 million annually for each factory. Polysaccharides from acidic water mainly contains homogalacturonan regions with ∼50% degree of esterification, whereas that from basic water was dominated with rhamnogalacturonan I regions with almost no esterification. The high viscosity of these branching polysaccharides, combined with gelling experiment results, suggested that both polysaccharides might be potential food thickening and gelling agents with large benefits to both the environment and the economy. Graphical abstract: Highlights: Pectic polysaccharides were recovered from citrus canning processing water. Water reuse system reduced water fee and the cost of polysaccharides recovery. The COD of effluent decreased dramatically through polysaccharides recovery. Recovered polysaccharides could be healthy food thickening and gelling agents.